Enterprise Internal Strategy at Management Information System “Khanza” Muhammadiyah Sidoarjo Hospital - Eka Risma Wahyuni; Rita Ambarwati; Misti Hariasih (School of Business, Bogor Agricultural University (SB-IPB), 2025)
Background: Management Strategy using SI/TI Strategy in operational management and logistics at Muhammadiyah Sidoarjo Hospital with the SIMRS Khanza application is one of the programs that supports active management and logistics at Muhammadiyah Sidoarjo Hospital. The primary objective is to know SIMRS Khanza's operational management and logistics performance to improve service quality.Purpose: Find the Management Strategy using IS/IT Strategy in operational and logistics management at Muhammadiyah Hospital Sidoarjo with the SIMRS Khanza application.Design/methodology/approach: This research uses a descriptive qualitative approach. According to Porter's Value Chain Model, the data collection and analysis stages used value chain analysis. The study results show that Muhammadiyah Sidoarjo Hospital needs to improve operational and logistical management by emphasising IS/IT strategic planning and developing hospital websites and medical records to support services, health services, administration, and research. Analysis of Porter's Value Chain Model explains that the Sidoarjo Muhammadiyah Hospital carried out two activities related to improving services at the Sidoarjo Muhammadiyah Hospital. Findings/Result: The main activities include Inbound logistics, Operations, Outbound Logistics, Marketing and Sales, and Service. Supporting activities include Firm Infrastructure, Human Resource Management, Technology Development, and Procurement. Muhammadiyah Hospital conducted two exercises to improve services at Muhammadiyah Sidoarjo Hospital.Conclusion: This study found that the main activities in service improvement include inbound logistics, operations, outbound logistics, marketing and sales, and service.Originality/value (State of the art): This study is original in applying Porter's Value Chain Model to analyse IS/IT strategy in operational and logistics management at Muhammadiyah Hospital Sidoarjo, primarily through implementing the SIMRS Khanza application. Keywords: IS/IT strategy, management hospital, management strategy, operational and logistics, value chain